The Legacy of ibn Sina's Thought on the Development of Islamic Psychology: A Historical Literature Review - Atmasari, Rina; Nur, Khariah; Utomo, Eny Indriastuti; Rahmayanti, Kurnia (Journal La Sociale, 2026)
This study examines the legacy of Ibn Sina’s psychological thought and its significance for the development of Islamic psychology through a historical philosophical literature review. As one of the most influential Muslim philosophers of the Islamic Golden Age, Ibn Sina developed a comprehensive theory of the soul (al-nafs) that integrates intellectual, emotional, and moral dimensions of human existence. Drawing primarily on his major works, including Kitab al-Nafs, Al-Shifa’, and Al-Najat, this research analyzes how his conceptualization of the vegetative, sensitive, and rational aspects of the soul provides a holistic framework for understanding human psychology. The study employs thematic content analysis to identify key psychological concepts in Ibn Sina’s writings and to examine their reinterpretation in contemporary scholarship on Islamic psychology. The findings indicate that Ibn Sina’s thought offers an alternative epistemological foundation to reductionist psychological paradigms by emphasizing the immaterial nature of consciousness, the central role of reason, and the ethical orientation of mental life. At the same time, the study highlights the need for critical engagement with his ideas to avoid anachronistic or normative applications in modern psychological practice. Overall, the research demonstrates that Ibn Sina’s psychological framework remains theoretically relevant for contemporary Islamic psychology, particularly in efforts to develop culturally grounded and ethically sensitive approaches to mental health and human development. This study contributes to the ongoing reconstruction of Islamic psychology by clarifying the philosophical roots of the discipline and by positioning Ibn Sina’s legacy as a valuable intellectual resource for future theoretical and interdisciplinary research.